Perception and behavior of small and medium-sized enterprises in adopting green innovation in Tacloban City Clara Marica Abala Aguilar, Justine Jose Merino Biagcong, [and] Queenstein May Elorde; Flordeliz B. Dacuyan, adviser. - Aguilar, Clara Marica Abala; Biagcong, Justine Jose M.; Elorde, Queenstein May A.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2023)
The Philippines is characterized by a high vulnerability to various climate-related events, which have significant implications not only for natural resources but also for the country's economic growth, particularly in relation to business operations. Small and medium-sized enterprises (SMEs) have been identified as contributors to environmental problems with potential harm to people, communities, and their own operations. Recognizing the importance of sustainable business practices, it is essential for companies to actively monitor and mitigate their environmental impact through green innovation. However, existing research has predominantly focused on large corporations, neglecting comprehensive information about SMEs, particularly in Tacloban City. Consequently, there is a need for additional research in this area. This study aims to learn how the perception and behavior of green innovations correlate.
This study aimed to investigate the influence of perception on the behavior of SMEs adopting green innovation in Tacloban City. Drawing upon the Lin and Ho (2011) Framework, the research employed a quantitative correlational research design and utilized a structured questionnaire. The sample comprised 50 SMEs from the food and service sectors, selected through a purposive sampling approach. Descriptive statistics and the Pearson correlation coefficient were employed for data analysis. The study revealed a significant relationship between perception and behavior in the adoption of green innovation, affirming the importance of understanding this dynamic for SMEs in the context of Tacloban City.
Undergraduate thesis (B.S. in Management) -- University of the Philippines, Tacloban.
Keywords: Green innovation -- Small and medium enterprise -- Environmental responsibility -- Tacloban City